Mechanisms Of Professional Development And Career Support In Student Mobility Programs - Khabibullaev Alimardon Khidoyatillayevich (Next Scientists International Journal EIJP, 2026)
This article investigates the multifaceted mechanisms of professional development and career support within the context of student mobility programs in higher education. In an era of globalization and increased academic mobility, the role of structured career guidance, mentoring, and skill enhancement initiatives has become paramount for fostering employability and professional growth among mobile students. By synthesizing contemporary research and policy frameworks, this study examines the pedagogical, institutional, and strategic dimensions of career support systems, emphasizing their impact on students’ competencies, adaptability, and career trajectories. Furthermore, the article explores how international exposure and cross-cultural experiences contribute to the development of transferable skills, resilience, and professional networks, thereby enhancing the overall effectiveness of mobility programs. The findings aim to provide actionable insights for educational institutions, policymakers, and stakeholders to optimize student mobility initiatives for sustained professional and career advancement.